Zagrożenia środowiska wynikające z nadmiernej konsumpcji - Dorota Strzyżewska (Studia Ecologiae et Bioethicae)
Results o f excessive consumption that have been presented in article can be expected and some have been already observad. Interpreted development o f mankind has caused it erroneously, that person corrects nature, it interferes in to its her right and secrets, there is that in environment natural destroying. That capability o f influence causes on whole planet, that there to be guilty interactive activity o f person programed prudently. Human is first biological sort on earth, which is  modify whole surface of planet to manner deep able very and global.